A retrospective analysis of the use of loteprednol etabonate ophthalmic suspension 0.5% following canaloplasty - Khaimi MA (Dove Medical Press, 2018)
Mahmoud A Khaimi Dean McGee Eye Institute, Oklahoma City, OK, USA Background: While loteprednol etabonate (LE) suspension 0.5% is approved for the treatment of postoperative ocular inflammation, there have been no reported studies of its use in glaucoma patients undergoing canaloplasty.Methods: This was a retrospective medical chart review conducted at a single US center. Data were collected on patients with glaucoma who underwent canaloplasty with or without cataract surgery, and were prescribed LE suspension 0.5% postoperatively. Outcomes evaluated included postsurgical inflammation (anterior chamber [AC] cells and flare), intraocular pressure (IOP), number of IOP-lowering medications, and postsurgical complications.Results: Data were collected on 204 patients (262 eyes) with a mean (SD) age of 71.6 (11.3) years. The most frequent LE dosing regimens at day 1, week 1, and month 1 postsurgery were QID (92.3%; 241/261), TID (52.6%; 133/253), and QD (65.5%; 78/119), respectively. Inflammation (AC flare and cells), mostly mild, was noted in 33.2% (86/259) of eyes on postoperative day 1 and 8.6% (21/244) of eyes at month 1. Mean IOP and mean number of IOP-lowering medications were significantly reduced from baseline (P<0.001) at all time points postoperatively. Complete (no IOP-lowering medication) or qualified (use of ≤2 IOP-lowering medications) surgical success was achieved in 78.8% and 90.6% of eyes, respectively, at month 6 and 63.4% and 92.7% of eyes at month 36. The most frequently observed postoperative complication was hyphema in 48.7% (126/259) eyes at day 1, which decreased to 0.4% (1/244) of eyes by month 1. IOP ≥30 mmHg was noted in 13 (5.3%) eyes at postoperative week 1 and rarely thereafter, and no patient discontinued therapy because of an IOP increase.Conclusion: These real-world data suggest that canaloplasty with or without cataract surgery managed postoperatively with LE suspension 0.5% is effective and safe in the glaucoma patient. Keywords: canaloplasty, loteprednol etabonate, postoperative inflammation, glaucoma, intraocular pressure